Identification and classification of local climate zones in a semi-arid city of Northwestern Mexico - Urias, Hiram Eduardo (Centro Universitario de Arte, Arquitectura y Diseño, 2020)
Most cities located in developing countries have expanded in a    disproportionate and irregular manner which favors the formation of areas with different characteristics called Local Climate Zones (LCZ), which promote the increase of intra-urban temperatures and the formation of the Heat Islands (HI). In semi-arid regions there are few researches that have conducted LCZ studies and its relation with the HI phenomenon. This study’s purpose was to carry out this classification and its relation with the increase in temperatures in the city of Mexicali, Mexico. Visual in-situ surveys, analysis by Geographic Information Systems (ArcMap and IDRISI), a categorization based on Stewart and Oke’s work (2012) and a comparison with the city´s thermal images were carried out to determine the relationship of the urban structure and the HI. The results can have an impact on urban planning, serve as a reference for authorities so they can establish critical points and develop policies that help reduce the population's mortality and morbidity. The results can also serve as a basis for designers that develop strategies that seek surface temperatures decrease; on the other hand, it is imperative to point out that the works of Stewart and Oke (2012) cannot be fully replicated and its application had to adjust to the city’s conditions.